Effect of oral nitrate supplementation on pulmonary hemodynamics during exercise and time trial performance in normoxia and hypoxia: a randomized controlled trial - Bourdillon, Nicolas; Fan, Jui-Lin; Uva, Barbara; Müller, Hajo; Meyer, Philippe; Kayser, Bengt (Frontiers in Physiology, 2015)
Background: Hypoxia-induced pulmonary vasoconstriction increases pulmonary arterial pressure (PAP) and may impede right heart function and exercise performance. This study examined the effects of oral nitrate supplementation on right heart function and performance during exercise in normoxia and hypoxia. We tested the hypothesis that nitrate supplementation would attenuate the increase in PAP at rest and during exercise in hypoxia, thereby improving exercise performance. Methods: Twelve trained male cyclists [age: 31 ± 7 yr (mean ± SD)] performed 15km time-trial cycling (TT) and steady-state submaximal cycling (50, 100, and 150 W) in normoxia and hypoxia (11% inspired O2) following 3-day oral supplementation with either placebo or sodium nitrate (0.1 mmol/kg/day). We measured TT time-to-completion, muscle tissue oxygenation during TT and systolic right ventricle to right atrium pressure gradient (RV-RA gradient: index of PAP) during steady state cycling. Results: During steady state exercise, hypoxia elevated RV-RA gradient (p>0.05), while oral nitrate supplementation did not alter RV-RA gradient (p>0.05). During 15 km TT, hypoxia lowered muscle tissue oxygenation (p<0.05). Nitrate supplementation further decreased muscle tissue oxygenation during 15 km TT in hypoxia (p<0.05). Hypoxia impaired time-to-completion during TT (p<0.05), while no improvements were observed with nitrate supplementation in normoxia or hypoxia (p>0.05). Conclusion: Our findings indicate that oral nitrate supplementation does not attenuate acute hypoxic pulmonary vasoconstriction nor improve performance during time trial cycling in normoxia and hypoxia.